The Correlation Between Betel Nut Consumption and Dental Health Status of The Community Within The Working Area of Camplong Health Center in Kupang District, East Nusa Tenggara - Serly Sani Mahoklory; Ferdinandus Suban Hoda; Welsin Kay (Proceeding of International Conference on Science, Health, And Technology, 2019)
Dental health is a reflection of the general health of each individual, because it is very important to maintain dental hygiene and health. A problematic or unhealthy tooth will be very disruptive, both from the function of speech, chewing and aesthetic functions that have an impact on one's activity and confidence.Betel is a term used to refer to the habit of chewing a mixture of leaves / betel, areca nut and lime which is a habit of the gathering community which is handed down from generation to generation and has become an inseparable part of people's lives. Besides consuming betel nut has become a culture of Timorese society and as a symbol of brotherhood. The aim is to determine the relationship between consuming betel nut and dental health status in the community of PuskesmasCamplong. The method used in this research isanalyticobservational method with cross sectional approach, the method of sampling in this study was carried out by using purposive sampling technique,the sample in this study amounted to 70 respondents. The results of this study indicate that there is a relationship between consuming betel nut and dental health status in the community of PuskesmasCamplong working area, based on the Spearman rank test results obtained calculation results ρ value = 0.011 is smaller than α = 0.05 then H0 is rejected and H1 is accepted . The conclusion is that there is a significant correlation between consuming betel nut and dental health status in the community of Puskesmas Camplong.